SPACE, ECONOMY AND TOURISM - Martins Filho, Jorge (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.956, 2020)
This paper presents the ability of tourism to reveal itself as a qualified activity to perform the insertion and economic rehabilitation of depressed spaces. In this way, we aim to understand the possibilities of transformation in the geographical space because of the introduction and development of services related to tourism. It was used for bibliographic research authors who develop scientific production in the areas of tourism, economy and geography. The use of geographical science is necessary from the understanding of this science as responsible for deepening in its object of study, the social space, the relationship between society and nature. In a planned way and through economic growth strategies, space is transformed into stage of actions that reinforce their imaginary character, where everything is related to the condition of merchandise